Proceedings of the 2011 Workshop on Data Mining for Medicine and Healthcare 2011
DOI: 10.1145/2023582.2023589
|View full text |Cite
|
Sign up to set email alerts
|

Gauging the internet doctor

Abstract: As more and more content is published and consumed online, it is imperative to know if an information nugget found on the Web is trustworthy or not. This is especially important for online medical information as it affects the most vulnerable group of users looking for medical help online. In this paper, we study the feasibility of automatically assessing the trustworthiness of a medical claim based on community knowledge, and propose techniques to assign a reliability score for an information nugget based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Like these studies, our findings indicate that users prefer to receive supportive and uplifting emotions through online health communities. Moreover, the sentiment tendencies identified in this study are similar to those found by Vydiswaran et al [26]. This highlights the significance of understanding the connection between users' health demands and emotional demands in order to improve the efficiency of information retrieval and explain information behavior.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Like these studies, our findings indicate that users prefer to receive supportive and uplifting emotions through online health communities. Moreover, the sentiment tendencies identified in this study are similar to those found by Vydiswaran et al [26]. This highlights the significance of understanding the connection between users' health demands and emotional demands in order to improve the efficiency of information retrieval and explain information behavior.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, some researchers have utilized Facebook data to analyze user emotional expression characteristics, identifying types of users who require emotional support and discussing the positive impact of such support [24,25]. Sentiment tendencies within the text are analyzed to study the relationship between users' health demands and emotional demands, which is crucial for enhancing information retrieval efficiency and explaining information behavior [26].…”
Section: Introductionmentioning
confidence: 99%
“…So far, the approaches to automatically assessing credibility of health-related information on social media has been limited to three studies (Viviani and Pasi, 2017a). Firstly, Vydiswaran et al (2011) used textual features to compute trustworthiness based on community support. They evaluated their approach using simulated data with varying amounts of invalid claims, defined as disapproved or non-specific treatments, e.g.…”
Section: Credibility Of Medical User-generated Contentmentioning
confidence: 99%